(untitled) (Praxis Educativa, 2012)
This paper reports a research project based on case-studies related to bullying practices in Spanish high schools. Our objective was to identify different cultural patterns having influence on the emergence of violent behaviors in centers located in economically deprived areas. ëLack of motivationí, ëlazinessí, ëdisruptionsí, and so on, are key terms and expressions that acquire different meanings depending on who uses them. We found two major groups of teachers: those who blame students for what they regard as studentsí failure, and those who believe that a different teaching approach should be employed with those students. Two different concepts of punishment- in the case of bullying incidents- were also clear: punitive or preventive. In the end, we concluded that exclusive concentration on curricular contents could turn high schools in part of the violence problem. As a contrast, identifying social and cultural problems could be part of the solution.